Nipsoft AB - Søilen, Klaus Solberg; Huber, Stefan (2004)
Abstract: A large part of graduate engineers are hired directly by corporations when they graduate from university. They typically spend most of their working life being employed. Only a few take the step into entrepreneurship and start their own business. One reason for this university may be that educated engineers are not properly trained to run a business of their own. Many emphasize their short term personal economic situation even though they have developed a competitive business idea while in university. The founder and owner of the recently started IT-firm Nipsoft AB, located in Sollefteå/Northern Sweden, tells the story of an exceptional career: Being an academically trained technician, he thought he might have to wait a long time before leading a corporation of his own. Under rather coin-cidental circumstances he was able to start his own business at the age of 29. After a short time of struggle, he now leads his data system developing company successfully. He believes that much of his achievements is due to the short economic education which he received in an independent organization. For students to start to think about the possibility of starting up companies they need to be taught how.